Youth Employability Pathways: A Theoretical Perspective on South Africa’s Labour Market Challenges - Simon Thabo Mahlaole (Journal of Economics Education and Entrepreneurship, 2026)
South Africa’s youth unemployment remains high and many young people struggle to move from first opportunities into stable work. This article offers a conceptual synthesis and proposes a Youth Employability Pathways Model, which explains outcomes as the interaction of three pillars: Human capital, institutional intermediation and market absorption. Drawing on recent South African evidence and theory, the paper argues that each pillar is individually insufficient yet jointly necessary and mutually reinforcing. The model treats equity as a structural parameter and emphasises feedback loops to raise conversion from placement to progression. The study contribution to literature is a testable, system-level account that reframes goals from short-term access to durable progression. Policy and practice implications include bundling credible signals with coordinated intermediation and sectoral absorption mechanisms, supported by transport, childcare, mentoring and health services. The paper sets an agenda for empirical testing using linked administrative and platform data to estimate the added value of integrated bundles over single-channel interventions.